Effect of Garlic Organic Sulfides on Gene Expression Profiling in HepG2 Cells and Its Biological Function Analysis by Ingenuity Pathway Analysis System and Bio-Plex-Based Assays - Chenghao Lv; Caiqiong Wang; Ping Li; Yiwen Huang; Xiangyang Lu; Meng Shi; Chaoxi Zeng; Si Qin (Mediators of Inflammation)
Garlic organic sulfides are dietary bioactive components with multiple biofunctions to prevent chronic diseases/inflammation and promote human health. DADS (diallyl disulfide), DATS (diallyl trisulfide), and DTS (diallyl tetrasulfide) are typical organic sulfides with similar structures from garlic. However, the structure-activity relationship of garlic organic sulfides remained unknown. The aim of the present study was to investigate the effect of DADS, DATS, and DTS on the gene expression profiling of human hepatocellular carcinoma cells (HepG2) by application of microarray and specialized analysis software, GO, Bio-Plex-based cytokines assay and IPA and analyze their structure-activity relationship according to antioxidant, anti-inflammatory, and metabolic-related properties. According to the microarray data, with the increase of S atom in garlic organic sulfides, its biological activity was gradually enhanced. In the general catalog of GO, garlic organic sulfides mainly affect biological process, molecular function, and cellular component. RT-qPCR results indicated that the microarray data is trustworthy, and the structure-activity analysis data found that more sulfur atoms have more powerful properties; thus, microarray data of DTS was preceded to the subsequent IPA analysis. The results of IPA analysis showed that the top 5 signaling pathways and molecular functions were disturbed by DTS; the molecular functions with the highest scores affected by DTS are cancer, cell apoptosis, and cell proliferation, which imply that the occurrence or metabolism of these diseases is related to the differential expression of the above-mentioned related genes and the activation of signaling channels, and the core of the most significant molecular network is inflammation. Finally, the results found that the secretions of 6 cytokines in macrophages were significantly inhibited by DTS treatment. This is the first study that analyzed the structure-activity relationship of garlic organic sulfides, which will provide useful genetic information for its multi-biofunction and promote their clinical application in the near future.